Keterampilan Komunikasi Efektif Pustakawan Referensi dalam Melayani Pemustaka di Perpustakaan UIN Sunan Kalijaga Yogyakarta - Musrifah Musrifah (IAIN Ponorogo, 2017)
Librarians in their profession in the library must have adequate knowledge in all fields. As we know that the task of librarians, reference librarians especially severe because it requires special skills because the information presented comes from a special collection. Therefore, a reference librarian should have the skills, one of which effective communication associated with their professionalism in carrying out its duties are to serve, assist, guide, and became a consultant for user information as well as the high demands of science should be mastered. This is what lies behind the author's research on effective communication skills in serving the reference librarian at the Library of UIN Sunan Kalijaga Yogyakarta. This study aims to determine the general effective communication skills, how to build effective communication and the factors that hinder effective communication skills in serving the reference librarian at the library of UIN Sunan Kalijaga Yogyakarta. The method used in this research is descriptive method with qualitative research approaches. The research results indicate that communication reference librarian in serving users are already skilled and effective. As for how to build effective communication is done by reference librarian in serving users is how to understand and fulfill the aspects of effective communication as a full relief, tolerance, respect / respect, empathy, caring, polite, caring, can be heard, clearly, trust, caring and humble attitude. The factors that hinder effective communication skills in serving the reference librarian at the library UIN Sunan Kalijaga Yogyakarta that psychological factors, systematic, and ecological.